Evaluasi dan Analisis Sisa Material Pada Proyek Pembangunan Gedung Kantor Bahasa Provinsi Gorontalo - Marina Dondo; Moh. Yusuf Tuloli; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
Materials play a significant role in determining the total project cost. Inefficient use of materials often results in waste materials, which can result in financial losses and negative impacts on the environment. Efforts to minimize construction material waste will help increase contractor profits and reduce environmental impacts. The research uses primary data collected through direct observation and interviews with responsible parties at the job site and calculates and analyzes the percentage of leftover construction materials using secondary data in the form of plan overviews and Budget Estimates Plans (RAB). The research findings indicated that over-ordering of materials, design changes, miscommunication, and volume miscalculation were the main factors causing the remaining materials. Efforts to reduce material waste include good material planning and management, worker training and supervision, and identification and recycling of materials that can still be used. The largest residual material costs were found in 3 materials with the highest percentage, namely multiplex with a percentage of 52.10%, iron Ø10 with a percentage of 16.18%, and iron Ø19 with a percentage of 9.72% of the total price of residual material costs IDR 78,839,000.